Pengukuran Usability Pada E-Learning Politeknik Negeri Jakarta - Rachmah Nanda Kartika; Emmidia Djonaedi (Prosiding Seminar Nasional Teknoka, 2020)
Covid-19 has impacted human activities around the world, including education. Teachingandlearning activities that were originally conducted face-to-face have turned into remote teaching andlearning activities or online lectures. To support the government's ef orts to prevent Covid-19 fromspreading further, the Jakarta State Polytechnic conducts its lectures using PNJ's E-learning media. Learning media systems can be considered reliable if they can fulfill user needs, such as the ease of usingtools in E-learning. E learning must be able to be used in both theoretical and practical subjects. Theresearch targets for this study are graphic engineering, packaging printing industry technology, mechanical engineering, building construction, and energy conversion. However, these practical learningcompetencies cannot be achieved as conducted on the of line lecture. To ensure that the teaching andlearning activities using PNJ E-learning can run ef ectively, we need to measure its usability. In this study, we use USE questionnaire tool as usability measurement. The research conducted on 150 respondents showed that the level of usability in PNJ e-learning was 0,609 this figure is included in the category of goodusability level. However, this value is still within the minimun score criteria for the good category. TheValue for each variable, namely the uselfulness variable of 71.4%, the easy of use variable of 72.8%, theeasy of learning variable of 48.25% and the satisfaction of 51.2% of the long distance learning process. theory and practice using E-learning,. E-learning system's components that are improved are thebigbluebutton, attendance, login, additional notification features for student assignments, and attendance.